Carvedilol, Bisoprolol, and Metoprolol Use in Patients With Coexistent Heart Failure and Chronic Obstructive Pulmonary Disease - Su, Vincent Yi-Fong (Medicine (Baltimore), 2016)
Beta (β)-blockers are under-prescribed in patients with heart failure (HF) and concurrent chronic obstructive pulmonary disease (COPD) due to concerns about adverse pulmonary effects and a poor understanding of the effects of these drugs. We aimed to evaluate the survival effects of β-blockers in patients with coexistent HF and COPD. Using the Taiwan National Health Insurance Research Database, we conducted a nationwide population-based study. Patients with coexistent HF and COPD diagnosed between 2000 and 2009 were enrolled. Doses of the 3 β-blockers proven to be beneficial to HF (carvedilol, bisoprolol, and metoprolol) during the study period were extracted. The primary endpoint was cumulative survival. Patients were followed until December 31, 2009. The study included 11,558 subjects, with a mean follow-up period of 4.07 years. After adjustment for age, sex, comorbidities, and severity of HF and COPD, bisoprolol use showed a dose–response survival benefit [low dose: adjusted hazard ratio (HR) = 0.76, 95% confidence interval (CI) = 0.59–0.97, P = 0.030; high dose: adjusted HR = 0.40, 95% CI = 0.26–0.63, P < 0.001] compared with nonusers, whereas no survival difference was observed for carvedilol or metoprolol. Compared with patients with HF alone, this special HF + COPD cohort received significantly fewer targeted β-blockers (108.8 vs 137.3 defined daily doses (DDDs)/person-year, P < 0.001) and bisoprolol (57.9 vs 70.8 DDDs/person-year, P < 0.001). In patients with coexisting HF and COPD, this study demonstrated a dose–response survival benefit of bisoprolol use, but not of carvedilol or metoprolol use.